Using Inclusive Socratic Method to Remove Barriers to Diverse Student Engagement in Law School Classrooms - Natalie Silver; Penelope Crossley (Legal Education Review)
The Socratic method has been a foundational pedagogical approach in legal education to elicit reasoned responses and effective arguments from students. While this technique is seen as an effective means of building critical thinking skills and challenging students to analyse complex legal concepts, it can also alienate and intimidate women and minorities. Indeed, research has shown that these negative impacts can have far-reaching implications for these students’ educational performance, wellbeing, and future in the legal profession. This paper draws upon the academic literature for fostering supportive and inclusive environments in diverse law school classrooms to design and test an innovative adaptation of the inclusive Socratic method. By adding embedded dialogic feedback, authentic assessment and collaborative activities to create a supportive and inclusive classroom environment for law students from diverse backgrounds, our model promotes equal opportunities and cohort-building, while also fostering individual empowerment and wellbeing. In doing so, this new model of teaching and learning also assists in providing a solution to gender, ethnicity, class and health disparities in educational performance and participation in the legal profession.